Structure optimization of CH3NH3PbI3 by higher-valence Pb in perovskite solar cells with enhanced efficiency and stability. (15th July 2020) - Liu, Bing; Cui, Rongli; Huang, Huan; Guo, Xihong; Zuo, Shouwei; Dong, Jinquan; Yao, Huanli; Li, Ying; Zhao, Dangui; Wang, Jiahao; Zhang, Jing; Chen, Yu; et al.
Highlights: Stronger Pb-I bond induced by Higher-valence Pb. Existence of high valence state lead induced by electron withdrawing groups. Pb 4+ doping improves superficial crystallization. Abstract: The crystal structure of perovskite has a significant influence on the photovoltaic performance and stability of perovskite solar cells (PSCs). Pb 4+ is introduced into CH3 NH3 PbI3 (MAPbI3 )-based PSCs by participating the octahedral [PbI6 ] 4- structure, then to induce the formation of stronger Pb-I bond and reduce [PbI6 ] 4- octahedron distortion, which would improve structural symmetry, decrease the degree of disorder and be beneficial to the crystallization of perovskites. Synchrotron based X-ray absorption fine spectroscope (XAFS) revealed that the existence of higher valence state lead could be realized by doping Pb 4+ directly or induced by electron withdrawing group, in consequence the [PbI6 ] 4- octahedral structure becomes more stable. Grazing incidence X-ray diffraction (GIXRD) especially demonstrates that Pb 4+ with appropriate proportion may well replace part of Pb 2+ to form an uniform phase in the primal perovskite structure to improve the crystallization on the surface and homogeneous out-of-plane (OOP) ordered crystal accumulation in the bulk, which is also important for improving the efficiency and stability of PSCs. As a result, a power conversion efficiency (PCE) exhibits a 42.1% increase with the doping of 0.03% PbF4 and 0.075% PCBM compared with a pristine device and its stability improves markedly after 30 days of storage in ambient atmosphere.